A Low-Producing Haplotype of Interleukin-6 Disrupting CTCF Binding Is Protective against Severe COVID-19 - Chen, Tao; Lin, Yu-Xin; Zha, Yan; Sun, Ying; Tian, Jinxiu; Yang, Zhiying; Lin, Shan-Wen; Yu, Fuxun; Chen, Zi-Sheng; Kuang, Bo-Hua; Lei, Jin-Ju; Nie, Ying-jie; et al. (mBio, 2021)
Overproduction of cytokine interleukin-6 (IL-6) is a hallmark of severe COVID-19 and is believed to play a critical role in exacerbating the excessive inflammatory response. Polymorphisms in IL-6 account for the variability of IL-6 expression and disparities in infectious diseases, but its contribution to the clinical presentation of COVID-19 has not been reported. Interleukin6 (IL-6) is a key driver of hyperinflammation in COVID-19, and its level strongly correlates with disease progression. To investigate whether variability in COVID-19 severity partially results from differential IL-6 expression, functional single-nucleotide polymorphisms (SNPs) of IL-6 were determined in Chinese COVID-19 patients with mild or severe illness. An Asian-common IL-6 haplotype defined by promoter SNP rs1800796 and intronic SNPs rs1524107 and rs2066992 correlated with COVID-19 severity. Homozygote carriers of C-T-T variant haplotype were at lower risk of developing severe symptoms (odds ratio, 0.256; 95% confidence interval,  0.088 to 0.739; P = 0.007). This protective haplotype was associated with lower levels of IL-6 and its antisense long noncoding RNA IL-6-AS1 by cis -expression quantitative trait loci analysis. The differences in expression resulted from the disturbance of stimulus-dependent bidirectional transcription of the IL-6 / IL-6-AS1 locus by the polymorphisms. The protective rs2066992- T allele disrupted a conserved CTCF-binding locus at the enhancer elements of IL-6-AS1 , which transcribed antisense to IL-6 and induces IL-6 expression in inflammatory responses. As a result, carriers of the protective allele had significantly reduced IL-6-AS1 expression and attenuated IL-6 induction in response to acute inflammatory stimuli and viral infection. Intriguingly, this low-producing variant that is endemic to present-day Asia was found in early humans who had inhabited mainland Asia since ∼40,000 years ago but not in other ancient humans, such as Neanderthals and Denisovans. The present study suggests that an individual's IL-6 genotype underlies COVID-19 outcome and may be used to guide IL-6 blockade therapy in Asian patients. IMPORTANCE Overproduction of cytokine interleukin-6 (IL-6) is a hallmark of severe COVID-19 and is believed to play a critical role in exacerbating the excessive inflammatory response. Polymorphisms in IL-6 account for the variability of IL-6 expression and disparities in infectious diseases, but its contribution to the clinical presentation of COVID-19 has not been reported. Here, we investigated IL-6 polymorphisms in severe and mild cases of COVID-19 in a Chinese population. The variant haplotype C-T-T , represented by rs1800796, rs1524107, and rs2066992 at the IL-6 locus, was reduced in patients with severe illness; in contrast, carriers of the wild-type haplotype G - C - G had higher risk of severe illness. Mechanistically, the protective variant haplotype lost CTCF binding at the IL-6 intron and responded poorly to inflammatory stimuli, which may protect the carriers from hyperinflammation in response to acute SARS-CoV-2 infection. These results point out the possibility that IL-6 genotypes underlie the differential viral virulence during the outbreak of COVID-19. The risk loci we identified may serve as a genetic marker to screen high-risk COVID-19 patients.